The effectiveness of methods and algorithms for detecting and isolating factors that negatively affect the growth of crops - Moldir Yessenova; Gulzira Abdikerimova; Talgatbek Ayazbaev; Gulden Murzabekova; Aisulu Ismailova; Zhanar Beldeubayeva; Aliya Ainagulova; Ayagoz Mukhanova (Institute of Advanced Engineering and Science, 2023)
This article discusses a large number of textural features and integral transformations for the analysis of texture-type images. It also discusses the description and analysis of the features of applying existing methods for segmenting texture areas in images and determining the advantages and disadvantages of these methods and the problems that arise in the segmentation of texture areas in images. The purpose of the ongoing research is to use methods and determine the effectiveness of methods for the analysis of aerospace images, which are a combination of textural regions of natural origin and artificial objects. Currently, the automation of the processing of aerospace information, in particular images of the earth’s surface, remains an urgent task. The main goal is to develop models and methods for more efficient use of information technologies for the analysis of multispectral texture-type images in the developed algorithms. The article proposes a comprehensive approach to these issues, that is, the consideration of a large number of textural features by integral transformation to eventually create algorithms and programs applicable to solving a wide class of problems in agriculture.